Strategi Kepala Madrasah Dalam Meningkatkan Mutu Pendidikan Di Mts Al-Ikhlas Setungkep - Abdurrahim (Al-Gafari : Manajemen dan Pendidikan, 2023)
Existence head of Madrasah in the institution education have very important role in develop and lead institution quality education. Because therefore, it takes a strategy for the principal in the madrasah increase quality education in schools to be quality and religious schools. As for goals study This is First, describe and analyze the steps of the madrasa head strategy in increase quality education at MTs Al-Ikhlas Setungkep. Second, describe and analyze factor supports and factors inhibitor in increase quality education at MTs Al-Ikhlas Setungkep. Study This use approach qualitative. Method data collection used researcher includes : Observation, interview, and documentation. Findings study show that : First ; the steps of the madrasa head strategy in increase quality education at MTs Al-Ikhlas Setungkep is with method increase teacher professionalism, do activity coaching special For participant educate achieve, optimize facilities and infrastructure education, implementation supervision in a manner routine, intertwine harmonious relationship with participant students, teachers, and with society . Second ; Factor supporters in increase quality education at MTs Al-Ikhlas Setungkep is with increase curriculum and learning, administration . organization madrasa institutions, facilities and infrastructure, personnel (teachers and staff), resources Power human resources (HR), financing, students, participation society and environment culture education. Whereas factor inhibitor in enhancement quality at MTs Al-Ikhlas Setungkep is facilities and infrastructure not enough adequate, materials Study teaching is still a minimum, the number of skilled teachers Still limited, limited availability of educational funds and the environment social participant educate not enough support.